(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
The situation of the Faculty of Medicine of Valladolid is analyzed, supporting it with objective data from the state, events and developments related to the period of the Second Spanish Republic. The analysis includes the verification of events that occurred in that period that influenced the teaching in those years at the Medical Training Center. On the other hand, the composition of the staff of the different chairs of the Faculty of Medicine, especially its teaching staff, is provided, taking as reference the beginning of the year 1936 before the end of the republican period.